PENGEMBANGAN MODEL MATEMATIKA SISTEM WAHANA UDARA MIKRO DENGAN SAYAP KEPAK - Prabu Menara, Gandi
This thesis discusses about the modelling and simulation of a simple flapping-wing micro aerial vehicle (FMAV). A mathematical model of the FMAV system is required for understanding and analyzing the dynamic characteristics of it. To obtain the mathematical model, multi-rigid body approach is used. At this stage, a simple 3 component FMAV configuration, consisting of 1 main body and 2 wings, is considered, on which some coordinate systems are attached to for defining the orientation and movement of each components. Using Newton’s law, the system equation of motion then is derived, by taking into account the inertial force generated by wing movement, the gravity force, and aerodynamic force, which is formulated using quasi-steady model. Further, based on the mathematical model, a computer simulation model is developed using MATLAB/Simulink application. The numerical model then is used for simulating the flight dynamic of the FMAV especially in symmetric level flight condition. The simulation is conducted to observe and evaluate the dynamic characteristics of the FMAV, and also to investigate the effect of wing motion variation has on the FMAV attitude and movement. The simulation results show that the wing mode of motions play key role in determining the attitude and movement of the FMAV. It can be observed that, to some extent, particular flight condition can be achieved using different type of wing